Pengkajian dan Penanganan Daerah Aliran Sungai Bagian Hulu dengan Pendekatan Model ANSWERS, Bagian 1 : Prediksi Air Limpasan - Suharyono Suharyono; Putu Sudira; Sukirno Sukirno (agriTECH, 1998)
The Area Nonpoint Sources Watershed Environment Response Simulation (ANSWERS) model as the distributed hydrologic model for the simulation of 10 scenarios of land uses is presented. The model is based on the assumption that at any point of watershed spatial, runoff volume is closely related to the hydrologic and physiographic processes such as, rainfall intensity, infiltration rate, soil moisture content, soil behaviour, land slope and vegetative cover. The discharge hydrograph of the model gave a good result and was statistically significant to the observed hydrograph.. Among the ten scenarios of land uses, the lowest peak discharge of 7.7. m3/second was obtained at the simulation of 80% of forest land, meanwhile the highest peak discharge of 33.36 m3/second was obtained when there was no forest land at the study area.